PENGARUH KINERJA KELEMBAGAAN TANI TERHADAP EKSISTENSI MODAL SOSIAL PETANI KEDELAI DALAM MENDUKUNG KEBERHASILAN PROGRAM UPSUS PAJALE DI KABUPATEN LAMPUNG TIMUR - LUCYANA TRIMO, SEPTIANA, YOSINI DELIANA, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
The role of agriculture in the economic development of this country is still very important, besides being a fuel provider, this sector also contributes significantly to the development of workforce which is expected to have an increase in the change in the level of poverty. The Ministry of Agriculture has a vision and mission in alleviating poverty by rolling out various forms of programs to increase capital for farmers. Farmers who have developed their level of education, improved changes in the economic and political structure, began to understand to form a farmer group that had the goal of obtaining and obtaining mutual assistance included in the agricultural program of the government, such as the UPSUS Pajale Program. Farmers who are members of farmer groups will strengthen the ability of their groups to manage and channel the Pajale UPSUS Program assistance that requires improving farm safety consisting of indicators; the role of members of farmer groups, suitability of group services, collectivity, and resolution of local wisdom that still requires in its farming activities. The success of farmer groups can not be separated from social capital which is the main foundation that must be owned by farmers as group members. Mangkuprawira (2010) describes the support of social capital in farmers such as social norms, mutual trust, networking, cooperation, mutual relations, participation, and commitment that will be directly connected to the success of the UPSUS Pajale (soybean) program being rolled out by the government, and seen from three indicators namely; successful output, successful results, and successful benefits. The UPSB Pajale Program in East Lampung Regency is held from February to March 2019. The data used are primary and secondary data with the Mix-method research method. The sampling technique used was the Proportional Stratified Random Sampling with a total sample of 140 farmers who were members of a farmer group receiving the 2017 UPSUS Pajale Kedelai Program in East Lampung Regency. Data processing is done qualitatively and quantitatively. Data is arranged qualitatively using descriptive analysis, while quantitative data is processed using Structural Equation Modeling (SEM) analysis, which uses the LISREL 8.80 program. The results showed the value of R2 = 0.71, which means that the second variable namely Farmer Institutional Performance and the Existence of Farmer Social Capital contributed 71 percent and was significant to the Success of the UPSUS Pajale Program in East Lampung Regency.Keywords: Farming Institution, Existence of Social Capital, and UPSUS Pajale Program